Pelatihan Sistem Informasi Terkait Media Pembelajaran Daring di Era pandemic Covid-19 (TK Banin 58 Salatiga) - Indra Ava Dianta; Ahmad Ashifuddin Aqham; Eko Siswanto (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this service is to provide counseling and training on the application of information systems in good schools, understand the making of online learning media, be able to apply the knowledge gained and be involved in managing school learning media as a learning tool. to provide an entrepreneurial mindset or entrepreneurship. With this training program, it is hoped that educators can implement the knowledge and information obtained to support the teaching and learning process.